Exploring the Role of Smellscape in Enhancing Landscape Perception: A Case Study in the University History Museum - Qing Liang; Shucan Lin; Linwei Wang; Fanghuan Yang (Buildings)
As the cultural importance of universities continues to grow, university museums have become key platforms for promoting university heritage and values. However, enhancing the visitor experience in these museums remains challenging. This study examines the effectiveness of smellscape in enhancing the visitor experience in university history museums, with a focus on how various scents impact visitors’ emotions. Using the Fuzhou University History Museum as a case study, the museum was divided into three distinct zones: the Historical Evolution Zone (HEZ), the Contemporary Development Zone (CDZ), and the Thematic Exhibition Zone (TEZ). Specific scents were selected for each area to evaluate their emotional impact, and data were gathered using electroencephalography (EEG) indicators, emotional questionnaires, and scent pleasure scales. The results indicated that calming scents like sandalwood and agarwood, used in the HEZ, convey a sense of historical depth but may also evoke negative emotions, whereas sage enhances positive feelings. In the CDZ, rosemary and mint significantly improve emotional states, while lemongrass exhibits weaker pleasantness and appears less suited for this area. In the TEZ, scents such as patchouli and orange blossom align well with future-oriented themes, demonstrating high levels of pleasantness and emotional value. Smellwalk interviews further validated the experimental results, revealing notable differences in the emotional impact of smellscape across different exhibit zones. A thoughtful selection of scents can enhance the cultural expression of spaces and effectively regulate visitors’ emotional experiences, strengthening the cultural resonance of museum environments. Future designers may consider incorporating olfactory elements into landscape design.